Fluid Balance Has Effects on the Length of Hospital Stay After Coronary Artery Bypass Grafting Surgery (Iranian Journal of Kidney Diseases, 2020)
Introduction. A vast range of factors cause adverse outcomes after coronary surgery. The goal of this study was to figure out if there was a relation between large volumes of fluid balance in patients who underwent coronary surgery and common complications after CABG. Methods. 130 candidates for on-pump CABG were enrolled in our study at Rajaie Cardiovascular Medical and Research Center in 2016. After calculating balance volume for each patient, they were divided into 3 groups; Group (1): fluid balance < 2000 mL, Group (2): fluid balance 2000-3000 mL, Group (3): fluid balance > 3000 mL. Some of the post-surgery complications were studied in these 3 groups. Since in similar studies, fluid overload has been investigated based on the patient’s weight gain after surgery or only on the basis of the patient’s fluid intake, we designed a study based on an accurate fluid balance measurement, which included the subtraction of the patient’s outputs and losses from their intakes. Results. Logistic Regression showed that fluid balance > 3000ml was the predictor of long mechanical ventilation [ (Odds Ratio (95% CI) = 4.6 (1.9 - 11.5), P < .05], more than 3 days of ICU stay [(Odds Ratio (95% CI) = 3.2 (1.09 - 9.6), P < .05], and longer hospital stay [Odds Ratio (95% CI) = 5.2 (1.9 - 14.08), P < .05]. There was no significant relation between AKI and fluid balance. Conclusion. Administration of large fluid volumes in CABG patients would lead to fluid accumulation and independently associated with prolonged mechanical ventilation, longer ICU stays and extended hospital stays.